2001
DOI: 10.1055/s-2001-17609
|View full text |Cite
|
Sign up to set email alerts
|

Sports Injuries in Floorball: A Prospective One-Year Follow-Up Study

Abstract: Two hundred and ninety-five licensed floorball players from Finnish premier to fifth division were observed prospectively for one season to study the incidence, nature, causes and severity of floorball injuries. During the study period, 100 out of the 295 (34 %) players sustained 120 injuries. Thirty-seven percent (73/199) of the male players and 28 % (27/96) of the females suffered from an injury. The injury rate was 1.0 per 1000 practice hours for both sexes. The injury rates per 1000 game hours were 23.7 fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
62
6
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(73 citation statements)
references
References 2 publications
4
62
6
1
Order By: Relevance
“…Lo¨fgren et al (1994) calculated an injury rate of 2.5 per 1000 playing hours for male and female players. Wikstro¨m and Andersson (1997) found a rate of 8.2 per 1000 floorball game hours for female players, and Snellman et al (2001) 1.0 per 1000 practice hours and 15.9 per 1000 game hours. In the present study, the injury rate was 1.8 per 1000 practice hours and 40.3 per 1000 game hours.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Lo¨fgren et al (1994) calculated an injury rate of 2.5 per 1000 playing hours for male and female players. Wikstro¨m and Andersson (1997) found a rate of 8.2 per 1000 floorball game hours for female players, and Snellman et al (2001) 1.0 per 1000 practice hours and 15.9 per 1000 game hours. In the present study, the injury rate was 1.8 per 1000 practice hours and 40.3 per 1000 game hours.…”
Section: Discussionmentioning
confidence: 97%
“…They reported that 16 (94%) of all injuries in female players were acute traumas. Snellman et al (2001) reported that overuse injuries were the most frequent injury type in female players. In our study, 70% of injuries were traumatic and 30% were from overuse.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, almost 40% of these players are 20 years old or younger. The proportion of overuse injuries associated with floorball varies from 17 to 30% [2,3,5,6] and the knee is the most common location for overuse injuries [2,5]. Although previous studies have investigated the occurrence of injury in floorball [2,3,6,7], all of them focused on adult players.…”
Section: Introductionmentioning
confidence: 99%
“…Use of artificial surfaces has increased in floorball venues in recent years, and this may partly explain the growing injury rate in this sports 9 10. The purpose of this prospective study was to compare the incidence of traumatic floorball injuries between two surfaces: artificial floors and wooden floors.…”
mentioning
confidence: 99%